ANALISIS PEMBERHENTIAN TIDAK DENGAN HORMAT SEBAGAI PEGAWAI NEGERI SIPIL - Azizah, Nida Indriani; Sitabuana, Tundjung Herning (Fakultas Hukum Universitas Tarumanagara, 2021)
Civil Servants (PNS) as state apparatus have a central presence in bringing policy components to the realization of national goals and national development. These components are accumulated in the form of distribution of duties, functions and obligations of Civil Servants (PNS). In accordance with the provisions of Article 87 paragraph (4) letter b of the ASN Law, and Article 250 letter b of Government Regulation Number 17 of 2020 concerning PNS Management, Civil Servants (PNS) are dishonorably discharged because